Comparative Assessment of Efficiency in Attracting European Funds by Regions of Eastern European Countries - Dan Lupu; Mircea Asandului (CES Working Papers, 2015)
In the current decentralization reforms and severe budget constraints faced by Eastern European countries, we consider as imperative to analyze the effectiveness of structural funds management at regional level. Therefore, the purpose of this study was to estimate the technical efficiency of attracting structural funds by the regions in Poland, Bulgaria and Romania, determining the factors that influence efficiency and its implications for local development. The calculations were based on the mathematical model Data Envelopment Analysis, the main source of data being EUROSTAT. The estimates confirm the strong need for systemic reforms in the organization and operation of the development regions: modification of current transfer system, strengthen financial autonomy and solve the problem of excessive fragmentation of administrative-territorial structure, all having a negative impact on the efficiency of absorption of European funds developing regions of analyzed states.
Keywords: A1; A2; 330; absorption capacity; European funds; DEA method; CEE countries